2017
DOI: 10.1039/c7ra01140g
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced temperature stability and exceptionally high electrical contrast of selenium substituted Ge2Sb2Te5 phase change materials

Abstract: (II) thin films were synthesized and compared to the pure telluride Ge 2 Sb 2 Te 5 . In situ X-ray diffraction (XRD) and in situ transmission electron microscopy (TEM) investigations revealed a remarkably increased stability of the as-deposited amorphous phase and crystalline phases, which is increased by a factor of 100 for compound (II) compared to established phase change materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…In situ STEM heating experiments were performed with a Gatan 652 double-tilt heating holder. Previous studies showed a stable temperature measurement [56,57]. A heating rate of 10 °C/min was applied, and the temperature was maintained for 10 min before the images were taken for each temperature plateau to minimize thermal drift and ensure a robust estimation of the sample temperature.…”
Section: Temperature-dependent Stem Analysismentioning
confidence: 99%
“…In situ STEM heating experiments were performed with a Gatan 652 double-tilt heating holder. Previous studies showed a stable temperature measurement [56,57]. A heating rate of 10 °C/min was applied, and the temperature was maintained for 10 min before the images were taken for each temperature plateau to minimize thermal drift and ensure a robust estimation of the sample temperature.…”
Section: Temperature-dependent Stem Analysismentioning
confidence: 99%
“…6(a) doping of GST thin lms with Sn as well as substitution of Te with Se have an enhancing effect on the optical contrast. 94,95 Overall, by tuning the degree of structural order regarding the vacancy distribution and the associated degree of electron localization as well as texture of GST phase change alloys, distinct differences in optical and electrical properties within GST alloys can be achieved. Consequently, a proper engineering of disorder in different GST phases might enable the realization of multilevel resistance/reectivity states accomplished by crystalline-to-crystalline phase changes, resulting in a drastic increase of the data storage density and reduction in the energy consumption of working devices, respectively.…”
Section: Optical Reectivitymentioning
confidence: 99%
“…GST has been of interest for optical storage applications 9 , but it has not been ideal for phase-change random access memory (PCRAM) applications due to its low crystallization temperature (Tc), poor data retention ability 10 and low resistance contrast. Se is a smaller and more covalent atom compared to Te and it is found that Se doping enhances the phase change properties of GST 11 – 15 . There are reports that Se alloys such as Ga-Sb–Se, Sb–Se possess higher Tc, better data retention, higher switching speed, lower thermal conductivity 16 , and lower melting temperature with respect to GST.…”
Section: Introductionmentioning
confidence: 99%